Respuesta :
Answer:
[tex]a_6_0=322[/tex]
Step-by-step explanation:
we know that
The rule to calculate the an term in an arithmetic sequence is
[tex]a_n=a_1+d(n-1)[/tex]
where
d is the common difference
a_1 is the first term
we have that
[tex]a_1=27\\a_2=32\\a_3=37\\a_4=42[/tex]
[tex]a_2-a_1=32-27=5[/tex]
[tex]a_3-a_2=37-32=5[/tex]
so
The common difference is d=5
[tex]a_4-a_3=42-37=5[/tex]
Find 60th term of the sequence
[tex]a_n=a_1+d(n-1)[/tex]
we have
[tex]a_1=27\\d=5\\n=60[/tex]
substitute
[tex]a_6_0=27+5(60-1)[/tex]
[tex]a_6_0=27+5(59)[/tex]
[tex]a_6_0=322[/tex]
The 60th term of the sequence should be 322 when the first four terms should be given.
Calculation of the 60th term of the sequence:
Since
a1 = 27
a2 = 32
a3 = 37
And, a4 = 42
So,
= 27 + 5(60 - 1)
= 27 + 5(59)
= 322
hence, The 60th term of the sequence should be 322 when the first four terms should be given.
Learn more about sequence here: https://brainly.com/question/24707075